The Mechanism of Avoiding Riba in Islamic Financial Institutions: Experiences of Indonesia and Malaysia - Muhammad Maksum; Nur Hidayah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The issue of discrepancy between business goals and sharia principles related to debt raises a problem. Financial institutions seek profit, but lending and borrowing money (qardh) in Islam is not for profit. This has the potential to generate usury (riba), and must be avoided by Islamic Financial Services (IFS). This article examines several Islamic legal opinions (fatwa) from the Indonesian National Sharia Council and the Malaysian Sharia Authority Council utilizing a normative and descriptive legal study approach, in conjunction with the science of Islamic jurisprudence (ushul fiqh). The results of the study outline that Islamic financial institutions must create products to avoid riba practices on unlawful debts. Two models for the creation of anticipatory riba were found by tracing and testing Islamic financial products using a credit schemes (qardh), namely entering into a service contract (ijarah) and conducting several transactions (bay' al-'inah) for one object. This product highlights the repetition of an old practice long-debated in classical fiqh because it is prohibited in a hadith of the Prophet Muhammad. This finding has implications for Sharia compliance as long as Sharia financial products do not shift to profit-sharing or buying and selling-based financial products.